“Current”, “heated rods” & “hot vapour”: Why patients refuse radiotherapy as a treatment modality for cancer in Northern Sri Lanka - Mahadevan, J.; Appudurai, R.; Shobikgha, S.; Kumar, R.; Chrishanthi, R. (Springer Berlin Heidelberg, 2023)
Purpose: Signicant proportions of patients either refuse or discontinue radiotherapy, even in the curative setting, leading to poor clinical outcomes. This study explores patient perceptions that underlie decisions to refuse/discontinue radiotherapy at a cancer care facility in northern Sri Lanka. Methods: An exploratory descriptive qualitative study was carried out among 14 purposively-selected patients with cancer who refused/discontinued radiotherapy. In-depth semi-structured interviews were transcribed in Tamil, translated into English, coded, and thematically analyzed. Results: All participants referred to radiotherapy as “current” with several understanding the procedure to involve electricity, heat, or hot vapour. Many pointed to gaps in information provided by healthcare providers, who were perceived to focus on side effects without explaining the procedure. In the absence of these crucial details, patients relied on family members and acquaintances to ll these information gaps, often based on second- or third-hand accounts of experiences with radiotherapy. Many felt pressured by family to refuse radiation, feared radiation, or felt ashamed to ask questions, while for others COVID-19 was an impediment. All but three participants regretted their decision, claiming they would recommend radiation to patients with cancer, especially when it is offered with curative intent. Conclusion: Patients with cancer who refused/discontinued radiation therapy have signicant information needs. While human resource decits need to be addressed in low-resource settings like northern Sri Lanka, providing better supportive cancer care could improve clinical outcomes and save resources that would otherwise be wasted on patient preparation for radiotherapy.
Keywords: Radiotherapy; Refusal; Discontinuation of treatment; Supportive care; Northern Sri Lanka